Conceptions of time in children treated for malignant cerebellar tumours. (September 2014) - Labrell, Florence; Kieffer, Virginie; Grill, Jacques; Dellatolas, Georges
Abstract Primary objective: Conceptions of time in children having survived malignant cerebellar tumours (CT) and healthy children matched for chronological age (HCCA) were compared, knowing that the cerebellum has been involved in time perception. Methods and procedure: Study participants included 20 children with CT (13 boys) and 20 HCCA (10 boys) aged 6–12 years. All children with CT were at least 1 year after the end of treatment without relapse. A time questionnaire (TQ) exploring duration of daily activities, time units, planning and diachronic thinking was used, as well as a video animation (VA) displaying cyclic and linear time. Main outcomes and results: Children with CT obtained similar results as HCCA for time units, planning and diachronic thinking, but showed more difficulties than controls in estimating the duration of daily activities and understanding linear and cyclic time concepts (VA). Conclusions: These findings are not in favour of impaired time conceptions in children with CT and are probably linked to the specific life experience among children treated for a malignant pathology, rather than to the role of the cerebellum in time processing.